Cover Image, Volume 52, Issue 3 - Yang, Bo‐Yu (Cell Prolif, 2019)
The cover image is based on the Original Article 5‐ARI induces autophagy of prostate epithelial cells through suppressing IGF‐1 expression in prostate fibroblasts by Bo‐Yu Yang et al., https://doi.org/10.1111/cpr.12590. Cover Image © Boyu Yang/Shanghai General Hospital. [Image: see text]